TREATMENTS FOR OVERCOMING DORMANCY OF BARLEY SEEDS - TUNES, Lilian Madruga de; BADINELLI, Pablo Gerzson; OLIVO, Franciéle; BARROS, Antonio Carlos Souza Albuquerque (Scientia Agraria, 2008)
The work was done with the objective of studying the efficiency of different treatments to overcome dormancy in barley seeds harvested in different periods. For that, were used seeds of the cultivars MN 721 and Scarlett, evaluated separately. The treatments were as follows: pre-cold temperature from 5 to 10 °C; pre-drying temperature from 30 to 35 ºC; pre-drying temperature of 50 °C; soaking of the germination test substratum in giberelic acid solution and seeds without treatment as a check. It was also used the tetrazolium test for evaluating seed viability. The statistical arrangement was in a random design and the analysis of variance was in a factorial 2 x 3 x 5 (two cultivars x three harvesting periods x 5 treatments for overcoming dormancy), with four replications per treatment. It was concluded that, among the treatments, the most efficient was the temperature of 5 to 10 °C. The intensity of dormancy and the harvesting period of barley seeds interferes, directly, in the efficiency of the treatments used for overcoming dormancy.